The transition of religion to culture in law and public discourse - Beaman, Lori G., author.
1 online resource.
Keywords: "This book explores the recent trend toward the transformation of religious symbols and practices into culture in Western democracies. Analyses of three legal cases involving religion in the public sphere are used to illuminate this trend: a municipal council chamber; a town hall; and town board meetings. Each case involves a different national context-Canada, France, and the United States-and each illustrates something interesting about the shape-shifting nature of religion, specifically its flexibility and dexterity in the face of the secular, the religious, and the plural. Despite the differences in national contexts, in each instance religion is transformed into culture or heritage by the courts to justify or excuse its presence and to distance the state from the possibility that it is violating legal norms of distance from religion. The cultural practice or symbol is represented as a shared national value or activity. Transforming the 'Other' into 'Us' through reconstitution is also possible. Finally, anxiety about the 'Other' becomes part of the story of rendering religion as culture, resulting in the impugning of anyone who dares to question the putative shared culture"--